Gender-specific differential expression of exosomal miRNA in synovial fluid of patients with osteoarthritis - Ravindra Kolhe (Nature Portfolio, 2017)
Abstract The pathogenesis of osteoarthritis (OA) is poorly understood, and therapeutic approaches are limited to preventing progression of the disease. Recent studies have shown that exosomes play a vital role in cell-to-cell communication, and pathogenesis of many age-related diseases. Molecular profiling of synovial fluid derived exosomal miRNAs may increase our understanding of OA progression and may lead to the discovery of novel biomarkers and therapeutic targets. In this article we report the first characterization of exosomes miRNAs from human synovial fluid. The synovial fluid exosomes share similar characteristics (size, surface marker, miRNA content) with previously described exosomes in other body fluids. MiRNA microarray analysis showed OA specific exosomal miRNA of male and female OA. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis identified gender-specific target genes/signaling pathways. These pathway analyses showed that female OA specific miRNAs are estrogen responsive and target TLR (toll-like receptor) signaling pathways. Furthermore, articular chondrocytes treated with OA derived extracellular vesicles had decreased expression of anabolic genes and elevated expression of catabolic and inflammatory genes. In conclusion, synovial fluid exosomal miRNA content is altered in patients with OA and these changes are gender specific.